Ièu, Bancel, oficièr d’Empèri, una singularitat literària - Daniel Ollive (Revue des Langues Romanes)
The novel Ieu, Bancel, oficièr d'Empèri confronts two stories that take place more than a century apart. The reader learns about the first story in the diary of a young captain of the strategic nuclear forces who decides to desert during the Euromissile crisis. He discovers the other in the correspondence of two Second Empire officers that he found, by chance, in the house where he was hiding and which he reproduced in his diary. These three officers have a common destiny: seized by doubt in the face of the course of History, initially irresolute, they gradually forge their own conviction and end up leaving the army to obey their brand new conscience. They are then traitors. Moving from one letter to another, from one era to another, from the diary to a letter and from a letter to the diary, following the complex architecture of the novel, the reader traces his own path while sharing their quest. In this way, he becomes convinced that heroism is not the victory over others but fidelity to oneself.